British Listeners c. 1780–1830. Issue 3 (12th December 2020) - Rowland, David
Abstract : Evidence from diaries and correspondence shows how 44 individual listeners experienced music in Britain during the years c. 1780–1830. The individuals were not united by social class, but each of them had the financial resources to gain access to operas, concerts and other performances enjoyed by the wealthiest in society. Crucial to an understanding of these listeners' reactions to music is an evaluation of their personal documents, which demonstrates how their evidence is shaped by genre, readership and a variety of cultural factors. Their descriptions of performances are used to show how London audiences, characterized in general by noise and commotion, contained a wide variety of listeners, ranging from those who appear to have attended largely for social reasons to those who reacted deeply to the music they heard. The evidence shows that those who listened intensely found greater satisfaction in more exclusive, private performances. It also shows that some listeners were deeply moved by what they heard, sometimes expressing their emotions through tears, in keeping with the culture of sensibility which thrived throughout the period. Other themes that emerge from the evidence include the role played by reminiscence in intensifying listeners' listening, and the strong reactions that were often elicited by the experience of novelty or otherness. Some listeners are shown to have had different reactions to music according to the social context in which it was heard or the repertoire that was performed.